A COMPARATIVE ANALYSIS OF THE IMPACT OF ENTREPRENEURS' EDUCATION ON THE IMPLEMENTATION OF BUSINESS STRATEGIES: Study of Sound and Lighting Vendor Business Actors in Malang City - Bagus Setiawan; Aniek Indrawati; Farij Ibadil Maula (Yayasan Education and Social Center, 2022)
Entrepreneurship education has become very important for people pursuing a career in business. The daily activities experienced by an entrepreneur become a critical part of the entrepreneurship education process. The emergence of competition in entrepreneurship is unavoidable. For this reason, every entrepreneur is always required to innovate creatively to bring up a business strategy. This study uses a qualitative research approach with a descriptive type of research. This research takes 3 locations: Esa Production, Bypass Event Production, and Joyo Division in Malang. A business unit engaged in providing services and entertainment needs in Malang City. Key informants in this study include (1) ESA Production Business Owner: Ahmad Saiful Ulum (2)Bypass the proprietor of an event production business: Zamzam Damayanto, (3) Joyo Division Business Owner: Yusuf Abidin, while the supporting informants in this study are (1 ) Employee/ Crew Esa Production: Rima, (2) Employee/ Crew Bypass Event Production: Eris Efendi, (3) Employee/ Crew Joyo Division: Dani. The data collection procedure used in this study was an in-depth interview. The results of this study state that entrepreneurial education is needed for sound business actors from an early age whether entrepreneurship education through a formal, family environment or environmental experience because as a plan that will don in the world of the sound system and lighting business. Meanwhile, in surviving the event equipment business in the current pandemic era, it is necessary to increase innovation and creativity through several business strategies